Small Molecule Potentiator of Adjuvant Activity Enhancing Survival to Influenza Viral Challenge - Saito, Tetsuya; Sako, Yukiya; Sato-Kaneko, Fumi; Hosoya, Tadashi; Yao, Shiyin; Lao, Fitzgerald S.; Shpigelman, Jonathan; Messer, Karen; Pu, Minya; Shukla, Nikunj M.; Chan, Michael; Chu, Paul J.; et al. (Frontiers in Immunology, 2021)
As viruses continue to mutate the need for rapid high titer neutralizing antibody responses has been highlighted. To meet these emerging threats, agents that enhance vaccine adjuvant activity are needed that are safe with minimal local or systemic side effects. To respond to this demand, we sought small molecules that would sustain and improve the protective effect of a currently approved adjuvant, monophosphoryl lipid A (MPLA), a Toll-like receptor 4 (TLR4) agonist. A lead molecule from a high-throughput screen, (N-(4-(2,5-dimethylphenyl)thiazol-2-yl)-4-(piperidin-1-ylsulfonyl)benzamide, was identified as a hit compound that sustained NF-κB activation by a TLR4 ligand, lipopolysaccharide (LPS), after an extended incubation (16 h). In vitro, the resynthesized compound (2D216) enhanced TLR4 ligand-induced innate immune activation and antigen presenting function in primary murine bone marrow-derived dendritic cells without direct activation of T cells. In vivo murine vaccination studies demonstrated that compound 2D216 acted as a potent co-adjuvant when used in combination with MPLA that enhanced antigen-specific IgG equivalent to that of AS01B. The combination adjuvant MPLA/2D216 produced Th1 dominant immune responses and importantly protected mice from lethal influenza virus challenge. 2D216 alone or 2D216/MPLA demonstrated minimal local reactogenicity and no systemic inflammatory response. In summary, 2D216 augmented the beneficial protective immune responses of MPLA as a co-adjuvant and showed an excellent safety profile.